Effects of Modulating Actin Dynamics on HER2 Cancer Cell Motility and Metastasis. Issue 1 (December 2018) - Nersesian, Sarah; Williams, Rodette; Newsted, Daniel; Shah, Kavan; Young, Stephanie; Evans, P.; Allingham, John; Craig, Andrew
Abstract Amplification of HER2 leads to development of HER2-positive (HER2+) cancers with high rates of metastasis compared to other cancer subtypes. The goal of this study was to probe the vulnerability of HER2+ cancer cells to a filamentous actin (F-actin) severing and capping toxin. The growth and viability of human HER2+ breast cancer (HCC1954) and ovarian cancer (SKOV3) cell lines were significantly impaired upon treatment with the marine macrolide mycalolide B (Myc B) at doses above 100 nanomolar. Further testing of Myc B in combination with the antibody-drug conjugate Trastuzumab-emtansine (T-DM1) led to improved killing of SKOV3 cells compared to either treatment alone. At sub-lethal doses, treatment of HER2+ cancer cells with Myc B resulted in rapid loss of leading edge protrusions and formation of aggresomes containing F-actin and the actin regulatory protein Cortactin. This correlated with robust inhibition of HER2+ cancer cell motility and invasion with Myc B treatment. In SKOV3 tumor xenograft assays, intratumoral injections of Myc B impaired HER2+ tumor growth and metastasis, with maximal effects observed in combination with systemic delivery of Trastuzumab. Metastasis of SKOV3 cells to the lungs following tail vein injection was also reduced by Myc B. Together, these findings provide rationale for targeting F-actin in combination with existing therapies for HER2+ cancers to reduce metastasis.